Wear resistance of friction pairs «neck-liner» with copper-containing coatings - Кубич, В.И.; Ивщенко, Л.И. (Problems of Tribology, 2014)
Results of tests on the durability of the materials of friction pairs of elements from the natural samples, cut from the ZMZ engine parts, ZIL in conditions close to their operational mode. Evaluated the tribological characteristics of the element of friction pairs taking into account the formation of the original coating on samples-necks of complex materials: bronze BrOF4-0,25, surface-active medium %, (at.): gallium 81, indium 19. For information about the nature of manifestations of anti-friction properties of the coating in the test samples in accordance with the proposed complex load cycles due to a change in lubrication regimes, the authors have not previously been known, received them and presented for the first time.